2021
DOI: 10.5080/u25553
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age, Gender and Education on Phonemic and Semantic Verbal Fluency

Abstract: Bu çalışmada, belli bir sürede ve belli bir kategoride sözcük üretilmesi esasına dayalı Sözel Akıcılık Testi için norm verilerinin elde edilmesi ve yaş, cinsiyet ve eğitim düzeyinin anadili Türkçe olan bireylerde sözel akıcılık üzerine etkisinin incelenmesi amaçlanmıştır.Yöntem: Öncelikle fonemik akıcılık testi için farklı zorluk derecelerinde 3 harf belirlenmesi amacıyla bir pilot çalışma yürütülmüştür. Semantik akıcılık testi için insan isimleri ve hayvan isimleri seçilmiş, dönüşümlü semantik akıcılık testi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…In patients with mild cognitive impairment and with AD, Kawano et al [ 36 ] found that years of education were significantly related to SF test scores, but not significantly related to PF test scores. Similar effects of years of education and age have been consistently reported in many languages [ 22 , 37 , 38 ]. One reason that might being interfering in the comprehension of age and education level, is the variability of cognitive reserve in adult population [ 39 ].…”
Section: Introductionsupporting
confidence: 78%
“…In patients with mild cognitive impairment and with AD, Kawano et al [ 36 ] found that years of education were significantly related to SF test scores, but not significantly related to PF test scores. Similar effects of years of education and age have been consistently reported in many languages [ 22 , 37 , 38 ]. One reason that might being interfering in the comprehension of age and education level, is the variability of cognitive reserve in adult population [ 39 ].…”
Section: Introductionsupporting
confidence: 78%
“…Repetition errors, as a form of perseverative error, are seen as signalling a failure in inhibition and self-monitoring (Crawford et al, 1998). This finding does not align with those of Erden Aki et al (2022), who reported no gender differences in repetition errors on a phonetic fluency task. Evidence regarding gender-based differences in cognition is, however, highly ambivalent and more work is needed to establish whether these have clinical significance.…”
Section: Discussionmentioning
confidence: 75%
“…Also as anticipated, years of education was significantly and positively related to and positively predicted overall COWAT performance and performance on the COWAT subscales, with more highly educated participants obtaining higher average scores than less educated participants. The impact that education has on word production has been reported (Aki et al, 2022;İlkmen & Büyükişcan, 2022;Nogueira et al, 2016) and seems to be consistent across cultures and languages (Oberg & Ramírez, 2006).…”
Section: Discussionmentioning
confidence: 78%
“…Visual memory was assessed with Wechsler Memory Scale‐Visual Reproduction Scale 1‐2 (Karakas et al., 1996; Wechsler, 1987). For assessment of verbal fluency and speed of verbal production Phonemic and Semantic Verbal Fluency Tests (Erden Aki et al., 2013; Lezak, 1995); for attention, motor speed and mental flexibility Trail Making Test A and B (Cangoz et al., 2009; Spreen & Strauss, 1998); for attention and motor impulsivity Go/no‐go Test (Bezdjian et al., 2009) and for attention and working memory Digit Span Test Part A and B were administered (Karakas et al., 1996; Wechsler, 1987).…”
Section: Methodsmentioning
confidence: 99%